2016
DOI: 10.1111/epi.13635
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory after temporal lobe epilepsy surgery in children: Do only mesial structures matter?

Abstract: Our findings provide evidence of significant risk factors for verbal memory decline in children, specific to left mesial temporal lobe epilepsy. Children who undergo left temporal lobe surgery that includes mesial structures may be most vulnerable for verbal memory decline, especially when language representation is localized to the left hemisphere and when preoperative verbal memory is intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
(110 reference statements)
0
20
0
2
Order By: Relevance
“…Postoperative neuropsychology testing was not performed, this being a limitation of the study. A recent retrospective study showed a decrease in verbal memory in children following left temporal lobe surgery that includes mesial structures, particularly when language representation is in the left hemisphere [34]. Importantly, that study did not find a correlation between seizure freedom and postsurgical decline in verbal memory.…”
Section: Discussionmentioning
confidence: 83%
“…Postoperative neuropsychology testing was not performed, this being a limitation of the study. A recent retrospective study showed a decrease in verbal memory in children following left temporal lobe surgery that includes mesial structures, particularly when language representation is in the left hemisphere [34]. Importantly, that study did not find a correlation between seizure freedom and postsurgical decline in verbal memory.…”
Section: Discussionmentioning
confidence: 83%
“…Better preoperative performance level and left‐sided (mesial) TL surgery have been shown to be associated with worse verbal memory outcomes in numerous studies; for example, Law et al compared 23 children who underwent TL surgery while sparing the mesial structures (TL) to 40 patients with temporal lobectomies that included resection of mesial structures (TL + M) regarding their memory and seizure outcomes. They found that greater declines were evident in children after TL + M resections within the language‐dominant hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the neuropsychological profile in paediatric cases, particularly in younger children, may not yield lateralizing or localizing signs. In teenagers with temporal lobe foci, the patterns are more similar to those described in adults, and thus similar approaches for interpretation and analysis of risk are appropriate (Law et al, 2017). It can be challenging to identify test measures that are normed across a wide age range from early childhood to late adolescence, which further complicates the comparison of results at different ages and longitudinal assessment of surgical outcomes.…”
Section: Consideration Of Special Populations Childrenmentioning
confidence: 99%